PELAYANAN PEMERINTAHAN YANG BERTANGGUNG JAWAB - Rahman, Khairul (Universitas Riau, 2017)
The demands of services that priority the needs and demands of society will be difficult to be realizedwithout the responbility of every apparatus government. The complain and even critics who oftendelivered about the low quality of public services at all levels has become the theme of dailyconversation. All the evidence for the low quality of service received by society. The importance ofbuilding responsilbe government services because the society has the right to obtain services thatprioritize the objectives development. This is based on the idea that the government is actually formedto provide services to the society and in fact the government to gain power in a democratic state is amandate of society. The organizations of government are often referred to as ?society of services?(public servant). In reality, not all officials government / administrators have realized the importanceof service. The closer relationship between the service with the responsibility, the lack ofundersatnding of the government apparatus for the importance of the service indicates the weakness ofthe responsibility of the apparatus government. The complaint from society of poor and disappointingservices from the government and the flow of stories power abus. One of the causes, of all that is thelack of government responsibility to the society. An understanding of how to bulid government servicesis responsibility.